Nutritional evaluation of top foliages for livestock feeding in semi arid region of India - SINGH, SULTAN; BHADORIA, B K; KOLI, PUSHPENDRA; SINGH, ARPANA (The Indian Journal of Animal Sciences, 2020)
Top foliages from 9 plants were evaluated for nutritional, anti-nutritional attributes and in vitro fermentation. Protein, NDF, ADF, cellulose and lignin contents varied. Protein fractions (PA, PB1, PB2, PB3 and PC) and carbohydrate fractions (CA, CB1, CB2 and CC) varied among foliages. Foliages total carbohydrates, non-structural carbohydrates and structural carbohydrates were 69.53, 33.34 and 36.20%, respectively. Lignin bound/unavailable carbohydrate fraction (CC) was lowest in Securinega virosa (13.58) and highest in Cassia fistula (53.44). Free condensed tannin (6.40), protein bound condensed tannin (9.34) and fibre bound condensed tannin (101.12 mg/g) differed. Tree foliages differed in total digestible nutrients (TDN), digestible energy (DE), metabolisable energy contents and net energy efficiency for maintenance (NEM), lactation (NEL) and growth (NEG). Foliages differed in gas and CH4 production with mean values of 205.75 and 31.8 ml/g DDM, respectively. Methane% of gas ranged 12.67–18.58, while loss of DE as CH4 varied from 6.64–13.70. Partition factor, short chain fatty acids (SCFA), microbial protein and efficiency of microbial protein differed and their values were 5.15, 2.51, 292.5 and 0.55, respectively. Results revealed that Moringa oleifera and Cnidoscolus aconitifolius had more CP, low fibre, more energy, TDN and SCFA and less CH4% of total gas.